Нeat exchange experimental research at hashing by mixers with the magnetic drive gear - Ружинська, Людмила Іванівна; Кузьменко, Катерина Василівна (Eastern-European Journal of Enterprise Technologies, 2012)
Apparatus with mixers with magnetic drives are widely used in chemical and pharmaceutical industry. . The authors present experimental data of the research of heat transfer processes in the time of liquid mixing in such apparatus